Social belonging, compassion, and kindness: Key ingredients for fostering resilience, recovery, and growth from the COVID-19 pandemic - Slavich, George M.; Roos, Lydia G.; Zaki, Jamil (Anxiety, stress, and coping, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has led to increases in anxiety, depression, posttraumatic stress disorder, burnout, grief, and suicide, particularly for healthcare workers and vulnerable individuals. In some places, due to low vaccination rates and new variants of SARS-CoV-2 emerging, psychosocial strategies for remaining resilient during an ongoing multi-faceted stressor are still needed. Elsewhere, thanks to successful vaccination campaigns, some countries have begun reopening but questions remain regarding how to best recover, adjust, and grow following the collective stress and loss caused by the pandemic. Here, we briefly describe three evidence-based strategies that can help foster individual and collective recovery, growth, and resilience: cultivating social belonging, practicing compassion, and engaging in kindness. Social belonging involves a sense of interpersonal connectedness. Practicing compassion involves perceiving suffering as part of a larger shared human experience and directing kindness toward it. Finally, engaging in kindness involves prosocial acts toward others. Together, these strategies can promote social connectedness and help reduce anxiety, stress, and depression, which may help psychologists, policymakers, and the global community remain resilience in places where cases are still high while promoting adjustment and growth in communities that are now recovering and looking to the future.